Factors associated with self-rated health among immigrant workers in South Korea: Analyzing the results of the 2020 survey on immigrants' living conditions and labor force - Kang, Soo Jin; Hwang, Jinseub; Kim, Dohyang; Kim, Bongjeong (Frontiers in Public Health, 2022)
Immigrants' health is an emerging public health issue worldwide. This study aimed to measure immigrant workers' self-rated health and identify the factors affecting it. Data were obtained from the nationwide 2020 Survey on Immigrants' Living Conditions and Labor Force in Korea. The data from 14,277 economically active immigrants who participated in the study were analyzed. Self-rated health was measured using one question and divided into dichotomized categories (good and poor). Multivariate logistic regression with a weighted sampling method was used to investigate associated factors, namely, individual, social, and living and working environment variables, and to evaluate the interaction effects with gender. Overall, 23.0% of the participants showed poor self-rated health. The odds ratios for poor self-rated health were high in participants who reported unmet healthcare needs (OR = 3.07, 95% confidence interval: 3.00–3.13) compared to those who reported other factors, followed by moderate job satisfaction (OR = 2.23, 95% confidence interval: 2.20–2.26) and unsatisfied residential environment satisfaction (OR = 1.80, 95% confidence interval: 1.74–1.86). Significant associations were found between self-rated health and most variables, including the interaction test (gender × residential environment satisfaction, education level, working hours, and length of residence). To enhance immigrants' health status, the Korean government must develop strategies to increase their access to healthcare services and minimize unmet healthcare needs. In addition, working conditions must be improved, specifically regarding long working hours and discrimination; furthermore, immigrants' living environments should be considered.